Residential Electrical Storage: Feasibility Study for Hybrid Residential PV/Battery Systems in Cyprus - Tillyros, Kypros; Komodromos, Michael; Lestas, Marios; Christofides, Nicholas (My University, 2024)
This paper presents a simulation study on integrating grid-connected photovoltaic (PV) systems with a potential to implement battery storage in residential settings. It analyses the performance and feasibility of such systems in enhancing self-consumption and energy export. The simulation model considers factors like household energy demand profiles, and PV output profiles. Through this analysis, it is anticipated to offer insights for homeowners, policymakers, and industry stakeholders on achieving greater energy independence and resilience. Finally, findings show that the attempt to effectively utilise battery storage in a residence while aiming for the most economically feasible system heavily depends on the load demand. It was observed that no matter the profile of the building or the energy utilisation, there is no significant change in energy costs. However, the results manifested an upcoming trend for utilising energy that will prove beneficial for costumers.
Keywords: Grid connected hybrid PV systems; Microgrids; Residential Energy Storage